O Diário das trans: representações de mulheres trans e travestis no Diário do Pará (1980-1990) - NASCIMENTO, Júlio Ferro Silva da Cunha (Universidade Federal do Pará, 2025)
The core of this investigation lies in the growing queer historiography, examining the representations of trans women and travestis in the newspaper "Diário do Pará" in the 1980s, a decade considered pivotal in shaping identities and gender expressions deemed deviating from heterocisnormativity. With the end of censorship under the military regime, pharmaceutical revolutions, and media interest, the newspapers point to a "fad" surrounding the figures of travestis, transsexuals, transformists, and other subjects categorized amid terminological and identity shifts, giving rise to constant social, economic, and ethnic tensions between media representation and the represented subjects. Therefore, as a theoretical and methodological approach, the present research employs queer theory, which aligns with Foucauldian notions of power and discourse as practice. Thus, in addition to a “against the grain” intention of the periodical sources, this study problematizes the strategies of control and resistance within regional media discourses concerning the mediatization of the bodies and experiences of trans women and travestis. This allows for an understanding of how transfeminine representation is diverse, marked by ambiguity, presented as a source of both physical and symbolic violence, where this ambiguity is presented as an essential factor for the fascination with transfeminine individuals in sections covering shows, criminal cases, international affairs, and politics.